Criterion-related validity of the 20-m shuttle run test in youths aged 13-19 years - Ruiz, J. R.; Silva, G.; Oliveira, N.; Ribeiro, J. C.; Oliveira, J. F.; Mota, J. (Journal of Sports Sciences, 2009)
We assessed the agreement between maximal oxygen consumption (VO2max) measured directly when performing the 20-m shuttle run test and estimated VO2max from five different equations (i.e. Barnett, equations a and b; Lger; Matsuzaka; and Ruiz) in youths. The 20-m shuttle run test was performed by 26 girls (mean age 14.6 years, s = 1.5; body mass 57.2 kg, s = 8.9; height 1.60 m, s = 0.06) and 22 boys (age 15.0 years, s = 1.6; body mass 63.5 kg, s = 11.5; height 1.70 m, s = 0.01). The participants wore a portable gas analyser (K4b2, Cosmed) to measure VO2 during the test. All the equations significantly underestimated directly measured VO2max, except Barnett's (b) equation. The mean difference ranged from 1.3 ml/kg·min (Barnett (b)) to 5.5 ml/kg·min (Lger). The standard error of the estimate ranged from 5.3 ml/kg·min (Ruiz) to 6.5 ml/kg·min (Lger), and the percentage error ranged from 21.2% (Ruiz) to 38.3% (Lger). The accuracy of the equations available to estimate VO2max from the 20-m shuttle run test is questionable at the individual level. Furthermore, special attention should be paid when comparisons are made between studies (e.g. population-based studies) using different equations. The results of the present study suggest that Barnett's (b) equation provides the closest agreement with directly measured VO2max (cardiorespiratory fitness) in youth.